Do rivermouths alter nutrient and seston delivery to the nearshore?. (November 2016) - Larson, James H.; Frost, Paul C.; Vallazza, Jon M.; Nelson, John C.; Richardson, William B.
Summary: Tributary inputs to lakes and seas are often measured at riverine gages, upstream of lentic influence. Between these riverine gages and the nearshore zones of large waterbodies lie rivermouths, which may retain, transform and contribute materials to the nearshore zone. However, the magnitude and timing of these rivermouth effects have rarely been measured. During the summer of 2011, 23 tributary systems of the Laurentian Great Lakes were sampled from river to nearshore for dissolved and particulate carbon (C), nitrogen (N) and phosphorus (P) concentrations, as well as bulk seston and chlorophyll a concentrations. Three locations per system were sampled: in the upstream river, in the nearshore zone and at the outflow from the rivermouth to the lake. Using stable oxygen isotopes, a water‐mixing model was developed to estimate the nutrient concentration that would occur at the rivermouth if mixing was strictly conservative (i.e. if no processing occurred within the rivermouth). Deviations between these conservative mixing estimates and measured nutrient concentrations were identified as rivermouth effects on nutrient concentrations. Rivermouths had higher concentration of C and P than nearshore areas and more chlorophyll a than upstream river waters. Compared to the conservative mixing model, rivermouths as a class appeared to be summer‐time sources of N, P and chlorophyll a . Substantial among rivermouth variation occurred both in the effect size and direction for all constituents. Using principal component analysis, two groups of rivermouths were identified: rivermouths that had a large effect on most constituents and those that had very little effect on any of the measured constituents. 'High‐effect' rivermouths had more abundant upstream croplands, which were presumably the sources of inorganic nutrients. Cross‐validated models built using characteristics of the rivermouth were not good predictors of variation in rivermouth effects on most constituents. For consumers feeding on seston and microbes and vascular autotrophs directly taking up dissolved nutrients, rivermouths are more resource‐rich than upstream riverine or nearby Great Lakes waters. Given declines over time in open‐lake productivity within the Great Lakes, rivermouths may contribute more productivity than their size would suggest to the Great Lakes food web.